Results of Endoscopic Radial Artery Harvesting in 1577 Patients. Issue 6 (November 2013) - Dimitrova, Kamellia R.; Dincheva, Gabriela R.; Hoffman, Darryl M.; DeCastro, Helbert; Geller, Charles M.; Tranbaugh, Robert F.
Objective: We reviewed 1577 consecutive patients undergoing coronary artery bypass grafting (CABG) using endoscopic harvesting of the radial artery (RA) to define our current results. Methods: Since 2000, we have performed endoscopic RA harvest on 1577 consecutive patients; 1476 patients had isolated CABG, and 101 patients had CABG and other procedures. The mean ± SD age was 59.4 ± 9.0 years; 80.2% were men and 40% had diabetes mellitus. All data were prospectively collected. All-cause mortality was determined using the Social Security Death Index. Results: There were nine in-hospital or 30-day deaths, for an operative mortality of 0.57%: mortality was 0.34% in isolated CABG and 3.85% in CABG/combined procedures. The overall estimated Kaplan-Meier survival at 1, 5, and 10 years was 99%, 95%, and 88%. In 37 patients, the RAs were not harvested or were not used for grafting because of a positive Allen test, extensive calcification or dissection, intramural hematoma, and scarring from previous arterial lines or catheterization. During postoperative follow-up, five patients (0.32%) were treated for incisional infection, and there were no ischemic hand complications. Three patients had a perioperative myocardial infarction in the RA graft distribution, and 15 patients had a coronary artery reintervention in the RA graft distribution. Two other patients had a percutaneous coronary intervention of their RAs. The overall RA patency at 10 years was 82%. Conclusions: Endoscopic harvest of the RA is an excellent minimally invasive conduit harvesting technique with minimal morbidity.